Irrigation privatisation in India: options, issues and experience - Saleth, R. Maria (1999)
Conceiving `private sector' broadly to include not only the corporate sector but also the consultancy and contracting firms, water users' associations, non-governmental organisations, and the general public, this paper evaluates the options for promoting private sector participation in canal irrigation management, discusses the major issues involved in actualising such options, recounts some recent initiatives on irrigation privatisation, and outlines the thrust and focus of a strategy for promoting irrigation privatisation in India. - Reproduced
Keywords: Privatization - India; Irrigation - India; Irrigation